THE USE OF NUMBERED HEAD TOGETHER (NHT) METHOD TO IMPROVE STUDENTS’ SPEAKING SKILL - Moh. Mahmud; Arifiyana Arifiyana (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
English is used as communication in the world. It becomes an international language. There are four skills in English, namely speaking, listening, writing, and reading. Because English is used for communication, automatically speaking is most important in communication. But in reality, speaking is the lowest of them, so that to face this problem there must be some ways and solutions to improve the students speaking skills by using the unjoyful in the teaching-learning process. In this case, the researcher used cooperative learning to improve speaking skills. This study uses Class Action Research. Classroom action research can improve the teaching and learning process of speaking in class. The Classroom Action Research has four steps to conduct research. They are Planning, Implementing, Observing, and Reflecting. Every step has a different activity. The researcher always undergoes this process because it is a procedure to obtain the data result. The researcher has examined the speaking skills in tenth-grade excellent class program Madrasah Aliyah Al Amiriyyah Blokagung. Class Action Research conducted as much as these two cycles can improve speaking skills in students with a percentage number that is on the test Pre percentage amount 29,9% after the first cycle studies with cooperative learning, the number of percentages increased to 54,2%, but the number still has not reached the minimum value criteria of success of 80%, thus continuing the cycle II and the results of 83,3%. That amount has reached the minimum value criteria of success. From the description of the results of a classroom action research can be concluded that, learning cooperative learning model can improve speaking skills in the grade ten featured program Madrasah Aliyah Al Amiriyyah Blokagung 2020/2021 school year.